Analisis Perbandingan Kinerja Keuangan antara BNI Konven-sional dengan BNI Syariah Menggunakan Rasio Keuangan - hutauruk, Rivaldo; Munte, Mei Hotma (Universitas HKBP Nommensen, 2025)
This research aims to determine the differences between BNI Conventional and BNI Syariah banks before the merger occurred in 2021 which was tested using the financial report documentation method listed on the stock exchange in the 2018-2020 period. This research was conducted using financial ratios, namely the Solvency ratio using the Capital Adequacy Ratio (CAR), the Liquidity ratio using the Loan On Deposit Ratio (LDR) and the Profitability ratio using Return On Assets (ROA). From the results of the comparison between conventional BNI banks and BNI Syariah banks, BNI Syariah banks were superior because they managed to get very healthy scores in terms of capital and better credit risk. Meanwhile, conventional BNI banks are only superior in terms of profit generation or profits they have